Resistant Starch Production Technologies-A Review - RAIGOND, PINKY; Ezekiel, Rajarathnam; Singh, Brajesh; Dutt, Som; Joshi, Alka; Khobra, Rinki (Potato Journal, 2016)
Due to increasing health awareness among consumers; food manufacturers, researchers and producers are aiming to develop functional foods with additional nutritional benefits along with providing basic nutrition. Glycemic index of food directly affects the blood sugar level and caused fatal health problems such as diabetes and obesity. Glycemic index of a food is inversely related to its resistant starch content, hence, food nutritionists are looking out for incorporation of resistant starch as a functional ingredient in variety of foods to increase the acceptability of food in terms of low glycemic foods. Resistant starch is gaining attention as functional ingredient due to its unique physiochemical and functional properties. Incorporation of RS in wide variety of products such as breads, cookies, muffins, pizza crust, tortillas, breakfast cereals and snack products are already being practiced. Production of RS at commercial level is required to meet the growing demand of it as a functional ingredient. Various techniques for production of resistant starch such as heat treatment, enzymatic treatment, heat and enzyme treatment and chemical treatment are being practiced. The RS products namely, Hi maize, CrystaLean, Novelose 240, Novelose 260, Novelose 300, C*Actistar, FibersymTM HA, FibersymTM 80ST, Nutriose FB, Fibersol 2, HylonR VII and Neo –amylose are available in market. These products are different forms of RS such as RS2, RS3 and RS4 and contain different concentrations of dietary fibres. This review covers the various techniques being followed for the production of resistant starch.